Relapsed or refractory central nervous system lymphoma successfully treated by glofitamab combined with lenalidomide - Peng, Yin-yin; Tang, Xiao-qiong (Frontiers in Oncology, 2025)
BackgroundCentral nervous system lymphoma (CNSL) is rare and aggressive, which has high rates of recurrence and fatality. At present, there does not exist any standard treatment for the relapsed/refractory (R/R) CNSL.MethodsWe retrospectively analyzed 4 patients with R/R CNSL, who were treated with gloftamab combined with lenalidomide between October 2024 and June 2025 at the First Affiliated Hospital of Chongqing Medical University. Treatment response was assessed by brain magnetic resonance imaging and cerebrospinal fluid cytology every two cycles.ResultsThe 4 R/R CNSL patients include 1 male and 3 females, with the mean age of 58 years (range: 51~69 years). Their clinical manifestations at relapse included headache, stupor, listlessness, lethargy, nausea, poor appetite, weak limbs, walking disorder, slurred speech and visual impairment. The mean relapse time was 5 months (range 3~8 months) after the last treatment. After 2 cycles of treatment, all patients achieved rapid remission (2 in CRu and 2 in PR), the overall response rate was 100% (4/4). They got deep remission after 4 cycles (3 in CR/CRu, 1 in PR). No patient experienced cytokine release syndrome, immune effector cell-associated neurotoxicity syndrome nor hematological toxicity of grade 3 or above. Neither liver nor kidney dysfunction was observed. No treatment discontinuation occurred due to adverse events.ConclusionsThe glofitamab-lenalidomide combination showed promising activity and excellent tolerability in R/R CNSL, potentially addressing the critical need for effective salvage regimens.